Impact of coastal inundation on ecology and agricultural land use case study in central Java, Indonesia - Marfai, Muh (Quaestiones Geographicae, 2011)
Focusing on the regional scale, this study provides information concerning the existing ecological problems associated with coastal inundation in the northern part of coastal area in Central Java Province, Indonesia. The objectives of this paper are to map the coastal inundation, to investigate the impact of coastal inundation on coastal environment and ecology, and to assess the impact of inundation on agricultural land use. An integration of techniques, namely neighborhood analysis, iteration operation, and superimposed analysis method has been applied to generate the digital map and to analyze the impact of inundation. Fieldwork measurement has been done using cross-profiling in order to observe the impact of inundation on the coastal ecosystem. Based on the scenario of 100 cm and 150 cm of inundation, the affected area is about 15 207.6 Ha and 16 687.31 Ha, respectively. Fishpond, dry farming and paddy field are the most affected agricultural areas due to coastal inundation.